Acquisition of Pitjantjatjara Clause Chains - Defina, Rebecca (Frontiers in Psychology, 2020)
In Pitjantjatjara, a central Australian Indigenous language, speakers typically describe sequences of actions using clause chaining constructions. While similar constructions are common among the world’s languages, very little is known about how children acquire them. A notable exception are the converb constructions of Turkish, which have been relatively well-studied. The present paper examines the acquisition of Pitjantjatara clause chaining constructions and compares this with the acquisition of Turkish converb constructions. Data is drawn from a naturalistic corpus recorded between 2016 and 2019. The corpus contains over 4000 utterances from 23 children aged between 10 months and 10 years, five of whom are recorded at multiple ages. The corpus also includes approximately 1600 utterances from 21 adults, aged between 16 and 70. Results show that the acquisition of Pitjantjatjara clause chains consists of three stages. Stage 1 features juxtaposition of finite verb forms. In Stage 2, children make regular use of clause chain morphology, but primarily for modification purposes. In Stage 3, clause chains are the preferred strategy for sequential actions as well as modification purposes. The initial use of verb juxtaposition followed by increasing use of dedicated morphology is consistent with findings for Turkish converb acquisition, with speakers of both languages utilizing dedicated forms from around 2;6 onwards. A notable difference between the acquisition of Pitjantjatjara clause chains and Turkish converbs is in the order of acquisition of semantic functions. In Turkish, children acquire temporal functions, such as sequential actions, before modifying functions, such as manner specification. In Pitjantjatjara, the order is reversed, with children first using clause chaining constructions for modification and simultaneous aspects of events before utilizing them to combine sequential actions. This raises questions regarding the distribution and relative timing of event combination and modification strategies.